Effect of casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) on bond strength of a universal adhesive to demineralized dentin - Atefeh Nemati-Karimooy; Reyhane Hosseinpour Sabet; Mehrzad Khorshid; Arsalan Shahri; Hamideh Sadat Mohammadipour (Mashhad University of Medical Sciences, 2024)
Objective: This study investigated the effect of casein phosphopeptide‑amorphous calcium phosphate (CPP‑ACP) on the shear bond strength (SBS) of a universal adhesive in self-etch mode to demineralized dentin.Methods: Seventy-five dentin specimens were randomly divided into five groups (n=15) as follows: Group 1, intact dentin; Group 2, demineralized dentin receiving no remineralization agent; and Groups 3-5, demineralized dentin receiving CPP-ACP for 30, 90, and 180 seconds, respectively. All groups were bonded by Adper Single Bond Universal adhesive in self-etch mode. After 24 hours, the SBS test was conducted, and failure modes were recorded. The data were analyzed by one-way ANOVA, Tukey post-hoc test, and chi-square test at the significance level of P<0.05.Results: The highest and lowest mean SBS values were observed in groups 1 (intact dentin: 29.58 ± 8.13 MPa) and 2 (demineralized dentin: 13.41 ± 4.85 MPa), respectively. ANOVA revealed a significant difference in SBS among the groups (P< 0.001). A pairwise comparison revealed that the SBS of demineralized groups (groups 2-5) was significantly lower than that of the intact samples (P< 0.05). Group 5, with CPP-ACP, applied for 180 seconds, showed a significantly higher SBS (20.74 ± 4.54 MPa) compared to group 2 (P< 0.05).Conclusions: Applying CPP-ACP paste for three minutes can increase the bond strength of the universal adhesive in self-etch mode to demineralized dentin, whereas shorter application times are not effective.